Recursive determination of the enumerator for sums of three squares - John A. Ewell (International Journal of Mathematics and Mathematical Sciences)
For each nonnegative integer n, r3(n) denotes the number of representations of n by sums of three squares. Here presented is a two-step recursive scheme for computing r3(n), n≥0.